Human Rights and the Rule of Law from the Perspective of Constitutional Democracy - Triana Putri Siregar; Sofia Zuhro Zein Pulungan (AT-TAFAHUM: Journal of Law, 2025)
In the context of modern democracy, human rights (HAM) serve as the primary foundation for creating a just and sustainable social life. A state based on the rule of law, which upholds the principle of the supremacy of law, plays a crucial role in ensuring the protection and enforcement of human rights. This concept emphasizes that all citizens, including the government, are subject to the same law, thus preventing abuse of power and discriminatory practices.In Indonesia, human rights values are embedded in the Pancasila and the 1945 Constitution, but their implementation still faces various obstacles such as corruption, social inequality, and violations against minority groups. This research uses a normative-juridical approach through literature review and conceptual analysis. The results indicate that strengthening the rule of law can be achieved through judicial independence, improved legal education, and active public participation. Furthermore, globalization also influences the alignment between human rights and the rule of law through various international instruments. Therefore, strengthening the rule of law is crucial for realizing a just and inclusive society.